GC/MS-Based Urine Metabolomics Study on the Ameliorative Effect of Xanthoceras sorbifolia Extract on Alzheimer's Disease in Mice. (17th September 2022) - Han, Rui; Wang, Min; Wang, Li; Zhang, Yichen; Li, Xin; Hou, Yijun; Yan, Jing; Pan, Xiaojing
Abstract : The cause of Alzheimer's disease, the most common type of dementia today, is still unclear, and in current research, there are no drugs that work relatively well. Therefore, the study for new drugs to treat Alzheimer's disease is an urgent research need. Research on the improvement of Alzheimer's disease with extracts of Xanthoceras sorbifolia has been increasing in recent years, but the mechanism is not fully understood. The experiments were conducted to validate the model and analyze the treatment effect through D-galactose and A β 25–35 induced dementia model mice, using the Morris water maze, to detect the learning behavior and brain tissue section to observe the hippocampal tissue structure of mice. We performed a nontargeted metabolomic analysis of the urine obtained from different groups of mice using gas chromatography-mass spectrometry. Fourteen potential biomarkers were identified in the mice's urine, outlining five metabolic pathways of interest. It was shown that the extracts of Xanthoceras sorbifolia may exert protective effects on mice in dementia models through energy metabolism, neuroinflammation, and antioxidants. This study reveals the potential pathogenesis of Alzheimer's disease and the possible therapeutic mechanism of Xanthoceras sorbifolia, suggests relevant biomarkers, and provides an additional basis for the clinical application of Xanthoceras sorbifolia .